Clinical features, disease severity, and outcomes of pertussis in hospitalized children: A retrospective study from Serbia - Mihail Basa; Jelena Visekruna; Tijana Grba; Aleksandra Paripovic; Marija Marsenic; Vladimir Petrovic; Aleksandar Sovtic (PLoS ONE, 2026)
Background Severe pertussis remains a major cause of morbidity and mortality in early infancy, particularly among unvaccinated and preterm infants who lack sufficient maternally derived antibody protection. This study aimed to identify clinical and laboratory predictors of severe disease and fatal outcomes in hospitalized infants and young children with PCR- or serologically confirmed pertussis. Methods We conducted a retrospective study of 107 pediatric patients hospitalized with pertussis at a tertiary care center in Serbia between 2015 and 2025. Clinical characteristics, laboratory parameters, and outcomes were analyzed. Logistic regression—including Firth’s penalized models where appropriate—was used to explore predictors of PICU admission, mechanical ventilation (MV), and mortality. Viral coinfections were assessed using multiplex PCR, and leukocyte dynamics were monitored through standardized follow-up testing. Results Thirteen children (12.1%) required PICU admission and 12 (11.2%) underwent MV. Five patients (4.7%) died; all were unvaccinated infants younger than 2 months of age. Prematurity was a strong independent predictor of PICU admission and MV. Higher absolute lymphocyte counts and an elevated neutrophil-to-lymphocyte ratio at admission were also associated with severe disease. Viral coinfection was documented in 22.4% of patients and was associated with increased mortality. In exploratory analyses, both viral coinfection and elevated N/L ratio were associated with fatal outcome; however, these findings should be interpreted with caution due to the small number of events. Conclusions Severe and fatal pertussis predominantly affected infants in the first months of life, especially those born preterm and those without maternal or postnatal vaccine-derived protection. Viral coinfection was associated with worse clinical outcomes. These findings highlight the importance of early identification of high-risk patients and support preventive strategies targeting early infancy, including maternal pertussis immunization.